Experimental Haemorrhagic Effect of Two-Domain Non-Glycosylated Tissue Factor Pathway Inhibitor Compared to Low Molecular Weight Heparin - Holst, Jan; Lindblad, Bengt; Matthíasson, Stefan E; Stjernquist, Ulf; Ezban, Mirella; Østergaard, Per B; Hedner, Ulla (Thrombosis and Haemostasis, 1996)
The glycosylated multivalent three-domain Kunitz inhibitor TFPI is a natural inhibitor of tissue factor-FVIIa complex in the presence of FXa. TFPI has an experimental antithrombotic capacity indistinguishable from LMWH in a prophylactic dose, regardless of glycosylation and of the third domain. An inherited equilibrium between antithrombosis and haemorrhage exists. The aim of the study was to evaluate whether a two-domain non-glycosylated TFPI (117QTFPI1−161) has a bleeding potential in a rat gastric mucosa model. Groups; placebo, LMWH (tinzaparin) 60 and 250 anti-Xa IU/kg and 117QTFPIM61−161 1.0 and 10.0 mg/kg, given i.v. (bolus injection), randomised double dummy design.All actively treated groups significantly prolonged both the bleeding volume (493-984 Μl) and the bleeding time (10-20 min) compared to placebo (41 Μl, 2 min). It was not possible to distinguish a difference between the lower dose of LMWH and 117QTFPI1−161 in either parameter (p = 0.23-0.71). The two doses of 117QTFPI1−161 caused elevation of plasma-TFPI, 18 and 150 times baseline value. Both LMWH doses (0.6-3.2 anti-Xa IU/ml) and both 117QTFPI1−161 doses (0.2-2.7 anti-Xa IU/ml), caused significant effect in the anti-Xa assay, however 117QTFPI1−161 significantly less. Only the largest dose of 117QTFPI1−161 caused significant prolongation in the APTT assay (34 s). Both doses of LMWH caused significant prolongation (60-300 s). LMWH was the only substance to prolong the dilute-PT assay.Non-glycosylated two-domain 1.0 mg/kg TFPI, yielding supra-physiological plasma concentration, has an experimental haemorrhagic potential indistinguishable from LMWH in a prophylactic dose. The effect mediated by this type of TFPI could primarily be due to an inhibition of FXa.